Arbitrarily primed polymerase chain reaction for fingerprinting the genotype identification of mutans streptococci in children with Down syndrome - Barone, Simone; Macedo, Claudia; Marin, José Moacir (Wiley, 2005)
This study investigated the possible intrafamilial similarity of mutans streptococcal strains in some families with a child with Down syndrome using chromosomal DNA fingerprinting. The isolates were genotyped using arbitrarily primed polymerase chain reaction with the OPA 02 and OPA 03 primers. The results showed that five children with Down syndrome harbored mutans streptococci genotypes different from those of their mothers. A matching of genotypes was observed within the control pair (mother/child without Down syndrome). After six months, new samples were collected from all participants. Analysis showed that samples from children with Down syndrome were colonized by a new strain of Streptococcus mutans that did not match the previously collected one. The results suggest the S. mutans indigenous bacteria change more than once in children with Down syndrome.
Keywords: Genotypic identification; Intra-familial transmission; Streptococcus mutans; bacterial chromosome; bacterial colonization; bacterial genome; bacterial transmission; bacterial virulence; bacterium isolate; chromosome analysis; controlled study; dental caries; DNA fingerprinting; Down syndrome; female; gene identification; genetic heterogeneity; genotype; human; male; polymerase chain reaction; school child; species differentiation; vertical transmission